Histologic and morphologic character of pediatric abdominal aortic developmental coarctation and hypoplasia - Heider, Amer; Gordon, David; Coleman, Dawn M; Eliason, Jonathan L; Ganesh, Santhi K; Stanley, James C (Journal of vascular surgery, 2022)
Abdominal aortic coarctation and hypoplasia are uncommon diseases, recognized most often in pediatric-aged individuals. Comprehensive studies regarding the pathologic spectrum of these aortopathies are nonexistent. This investigation was undertaken to better define the histologic and morphologic character of abdominal aortic narrowings affecting children and assess its potential relevance to contemporary clinical practice. Aortic specimens obtained during open operations in children being treated for symptomatic, noninflammatory abdominal aortic narrowings at the University of Michigan were subjected to histologic study after hematoxylin and eosin, Movat, Verhoeff Van Gieson, and Masson's trichrome preparations. Microscopic findings were correlated with the anatomic aortic images. In addition, a detailed review was completed of all prior reports in the English literature that included images depicting the histologic character of noninflammatory abdominal aortic narrowings in children. Among a series of 67 pediatric-aged individuals undergoing open surgical interventions for abdominal aortic narrowings, eight children ranging in age from 9 months to 18 years, had adequate aortic tissue available for study. The loci of the specimens paralleled the anatomic sites of segmental coarctations observed in the entire series, with involvement of the suprarenal abdominal aorta (n = 3), intrarenal aorta (n = 2), and infrarenal aorta (n = 1). Diffusely hypoplastic abdominal aortas (n = 2) included one case of a de facto aortic duplication, represented by a channel that paralleled the narrow native aorta and gave origin to celiac artery branches, as well as the superior mesenteric and renal arteries. Concentric or eccentric intimal fibroplasia was observed in every aorta, often with internal elastic fragmentation and duplication (n = 4). Media abnormalities included elastic tissue disorganization (n = 3) and focal medial fibrosis (n = 1). Organizing luminal thrombus occurred in two infants. Coexistent ostial stenoses of the celiac, superior mesenteric, or renal arteries were observed in all but the only child who had an infrarenal aortic coarctation. Neurofibromatosis type 1 affected one child whose histologic findings were indistinguishable from those of the other children. A review of prior published histologic images of abdominal aortic coarctation and hypoplasia affecting children from other centers revealed a total of 14 separate reports, each limited to single case photomicrographs, of which 11 exhibited intimal fibroplasia. Intimal fibroplasia is a common accompaniment of developmental abdominal aortic coarctation and hypoplasia. It is posited that intimal fibroplasia, which is likely progressive in instances of abnormal shear stresses in these diminutive vessels, may contribute to less salutary outcomes after endovascular and certain open reconstructions of pediatric abdominal aortic narrowings.